PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPATU VENTELA PADA MAHASISWA/I FAKULTAS EKONOMI UNIVERSITAS YOS SOEDARSO - Mahmudah, Dewi Siti; Sitorus, Victor Glorimaruli Tua (Sekolah TInggi Ilmu Administrasi dan Manajemen Kepelabuhan (STIAMAK) Barunawati Surabaya, 2024)
Abstract. This research was conducted with the aim of finding out how much influence product quality, price and promotion have on purchasing decisions for Ventelapada shoes for students at the Faculty of Economics, Yos Soedarso University. The research method used is the associative analysis method, and uses the multiple regression analysis method. The data used in this research are primary and secondary data. The sample in this study was 97 consumers with a sampling technique using accidental sampling. The results of this research show that partially product quality, price and promotion have a positive and significant effect on purchasing decisions for Ventela shoes among students at the Faculty of Economics, Yos Soedarso University.